2022
DOI: 10.3390/ijerph19031089
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Expansive Learning in the Context of Healthy Ageing—A Formative Intervention between Dental Care and Municipal Healthcare

Abstract: There are great risks of diseases in the ageing population, and oral diseases are no exception. Poor oral health has profound negative impacts on the quality of life. It is therefore crucial to include the oral health perspective in the care for older adults. To meet the challenges associated with oral health in the ageing population, a formative intervention was launched. The intervention, called the TAIK project (=“Dental hygienist in a municipality organization”, in Swedish: Tandhygienist i kommunal verksam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…Three nursing assistants worked as oral care aides with some responsibility for oral health care work at their wards [ 21 ] and were interviewed in a separate group due to their special knowledge and experiences of the oral care cards. In another group interview, a dental hygienist and a strategist in municipal health care were interviewed together, as they belonged in an already existing collaborative intervention in the municipality [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three nursing assistants worked as oral care aides with some responsibility for oral health care work at their wards [ 21 ] and were interviewed in a separate group due to their special knowledge and experiences of the oral care cards. In another group interview, a dental hygienist and a strategist in municipal health care were interviewed together, as they belonged in an already existing collaborative intervention in the municipality [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Guided by the KTA framework (40), the four first action phases describe already conducted actions, and the three last action phases describe planned actions, evaluations and a plan for implementationthe randomized controlled trials is described in the sixth phase. Phase I: Identifying the problem or gap that needs attention, and identifying, reviewing and selecting the knowledge that can solve that problem or gap Within a collaborative project between dental and municipal care organizations (in Swedish; "the TAIK-project"), an interprofessional infrastructure for learning at work and being able to plan, perform and follow up on an interorganizational level enabled healthy ageing (7,42,45). It was concluded that oral care cards were difficult to use within the dental care remuneration programme and that patient safety therefore needed improvement (7,8).…”
Section: Procedures Of Interventionmentioning
confidence: 99%
“…The phases were also integrated in the shared paper-based prototype for a new 'oral care card' on a digital platform. The prototype was developed based on previous studies (34,55). No prior educational efforts were conducted on how to implement the phases within the oral assessments and the paper-based prototype, and all phases were performed in collaboration decided within the teams.…”
Section: Oral Assessmentsmentioning
confidence: 99%